DEMOCRATIC VALUES AND DIGITAL SKILLS OF STUDENTS IN HIGHER EDUCATIONAL ESTABLISHMENTS OF POLAND AND UKRAINE - Mariya Leshchenko; Larysa Tymchuk; Nataliia Pavlenko; Larysa Ruban (Novìtnâ Osvìta, 2020)
The subject of the paper is evaluating and comparing the activity of using digital technologies for the realisation of democratic values by students of Polish and Ukrainian higher educational establishments: rights to freedom of access to information; tolerant communication with other people; awareness of the values of solidarity, equality.The study was carried out at Maria Curie-Sklodowska University in Lublin (Poland), The Jan Kochanowski University in Kielce (Poland), Radom Academy of Economics (Poland), Taras Shevchenko National University of Kyiv (Ukraine), Poltava V.G. Korolenko National Pedagogical University (Ukraine). Based on the survey results, the quantitative and qualitative analysis of digital technologies used in the development of democratic ideals and social activity of youth are carried.The results obtained are typologically common for students of both Polish and Ukrainian higher educational establishments.The paper provides recommendations for teachers of higher educational establishments on the use of digital technologies to support the development of students’ democratic values in formal and non-formal learning and draws attention to the problem of forming digital critical competence of students.